Written Homework 4
Written Homework 4
Problem 1
Let {an } be a sequence defined by
a0 = 2
and
ak = 3ak−1 + 2 for each integer k ≥ 1.
We aim to prove by induction that
an = 3n+1 − 1
Proof by Induction
We will use mathematical induction to prove that an = 3n+1 − 1 for all n ≥ 0.
Base Case
For n = 0, we have a0 = 2. According to the formula,
a0 = 30+1 − 1 = 31 − 1 = 3 − 1 = 2.
Inductive Hypothesis
Assume that the formula holds for n = k, i.e., assume
ak = 3k+1 − 1.
We need to show that this assumption implies the formula holds for n = k + 1,
i.e.,
ak+1 = 3(k+1)+1 − 1 = 3k+2 − 1.
1
Inductive Step
Using the recurrence relation, we have
ak+1 = 3ak + 2.
ak+1 = 3(3k+1 − 1) + 2.
This is exactly the formula we wanted to prove for ak+1 . Therefore, assuming
the formula is true for n = k implies that it is also true for n = k + 1.
Conclusion
By the principle of mathematical induction, we conclude that
an = 3n+1 − 1
2
Problem 2
Let {dn } be a sequence defined by
d0 = 0, d1 = 4
and
dk = 6dk−1 − 5dk−2 for every integer k ≥ 2.
We aim to prove by induction that
dn = 5n − 1
Proof by Induction
We will use mathematical induction to prove that dn = 5n − 1 for all n ≥ 0.
Base Cases
We need to verify the formula for the initial values n = 0 and n = 1.
Case n = 0
For n = 0, we have d0 = 0. According to the formula,
d0 = 50 − 1 = 1 − 1 = 0.
Case n = 1
For n = 1, we are given d1 = 4. According to the formula,
d1 = 51 − 1 = 5 − 1 = 4.
Inductive Hypothesis
Assume that the formula holds for n = k and n = k − 1; that is, assume
dk = 5k − 1
and
dk−1 = 5k−1 − 1.
We need to show that this assumption implies
dk+1 = 5k+1 − 1.
3
Inductive Step
Using the recurrence relation, we have
dk+1 = 6 · 5k − 6 − 5 · 5k−1 + 5.
dk+1 = 5k+1 − 1.
Conclusion
By the principle of mathematical induction, we conclude that
dn = 5n − 1